Development of an EORTC quality of life phase III module measuring cancer‐related fatigue (EORTC QLQ‐FA13). Issue 5 (4th May 2012) - Weis, Joachim; Arraras, Juan Ignacio; Conroy, Thierry; Efficace, Fabio; Fleissner, Claudia; Görög, Attila; Hammerlid, Eva; Holzner, Bernhard; Jones, Louise; Lanceley, Anne; Singer, Susanne; Wirtz, Markus; et al.
Abstract: Background: European Organisation for Research and Treatment of Cancer (EORTC) has developed a new multidimensional instrument measuring cancer‐related fatigue that can be used in conjunction with the quality of life core questionnaire, EORTC QLQ‐C30. The paper focuses on the development of the phase III module, collaborating with seven European countries, including a patient sample of 318 patients. Methods: The methodology followed the EORTC guidelines for developing phase III modules. Patients were assessed by questionnaires (EORTC QLQ‐C30 with the EORTC Fatigue Module FA15) followed by an interview, asking for their opinions on the difficulty in understanding, on annoyance and on intrusiveness Results: The phase II FA15 was revised on the basis of qualitative analyses (comments of the patients), quantitative results (descriptive statistics) as well as the multi‐item response theory analyses. The three dimensions (physical, emotional and cognitive) of the scale could be confirmed Conclusions: As a result, EORTC QLQ‐FA13 is now available as a valid phase III module measuring cancer‐related fatigue in clinical trials and will be psychometrically improved in the upcoming phase IV. Copyright © 2012 John Wiley & Sons, Ltd.